Structural models of the paremiological units with the modality component in Spanish, English, and Tatar language (Revista de Investigaciones Universidad del Quindío, 2022)
This present study is focused on the comparative analysis of the grammatical and structural characteristics of paremiological units (PUs) with a modality element in Spanish, English, as well as the Tatar language. PUs with that element is absorbing for analyzing the linguistics worldview of Spanish, English, and Tatar language. This study’s relevance is defined by the reality that PUs are among the most contradictory and complex notions in linguistics. The subject of the study is related to linguistics to recognize the structure and features of PUs of Spanish, English, and also Tatar language. To fulfil the study’s aims, a descriptive-analytical method is utilized. This study revolves around the structural - lexical and structural - grammatical characteristics of the PUs expression of the compared tongues. The particular and general sorts utilizing the modality component of the linguistic worldview are determined, and their classification as well. The study outcomes provided are highly interesting to scientists examining the notions of PUs in Spanish, English, and Tatar language. The results have the capacity to be employed in the analysis and study of research and cultural issues and language learning procedure.
Keywords: component; modality; linguistics; paremiological units; culture